2022
DOI: 10.3389/fpsyg.2022.958945
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for MOOC learning persistence: An expectancy–value theory perspective

Abstract: Managing learning continuity is critical for successful MOOC learning. Thus, enabling learners to have learning persistence needs to be integrated into the MOOC learning design. Motivation effort is a critical component enabling students to maintain continuous MOOC learning. The expectancy–value theory explains why learners engage in learning: (1) they have a higher perceived ability for learning success, (2) place value on learning, and (3) avoid psychological costs. However, it is unclear how these factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 68 publications
0
8
1
Order By: Relevance
“…For other researchers, the development of motivational processes is significant from an integrative standpoint (Skinner et al, 2009). Various factors, such as the influence of the environment, self-concept, the learning process itself, and performance, contribute to its formation (Lee & Song, 2022). The author's own research demonstrated that students were more interested in MOOC courses during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For other researchers, the development of motivational processes is significant from an integrative standpoint (Skinner et al, 2009). Various factors, such as the influence of the environment, self-concept, the learning process itself, and performance, contribute to its formation (Lee & Song, 2022). The author's own research demonstrated that students were more interested in MOOC courses during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…One such idea might be breaking the course down into smaller units for easier assimilation or providing additional visual aids (Padilla Rodriguez et al, 2020). International observations also emphasize the importance of proper guidance before the start of the course, creating a learning-conducive environment, and delivering high-quality content (Gupta & Maurya, 2022;Lee & Song, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of self-efficacy has been examined in MOOC studies. Most studies identified self-efficacy as one of the significant predictors or moderators for learning outcomes in a MOOC environment, such as academic success [31], completion rate [32], perceived effectiveness of MOOC [33], MOOC learners' learning persistence [34], and increased motivation level [35]. Some other studies investigated the sources of MOOC learners' self-efficacy [36].…”
Section: Research Gaps and Research Questionsmentioning
confidence: 99%
“…The pedagogical approaches during the COVID-19 pandemic have primarily shifted to online platforms, creating a blended learning environment. This sudden shift has required educators to rethink strategies to maintain a learning environment that is conducive to student motivation (Lee & Song, 2022). Recent empirical work, such as the study by Chin et al (2022), underscores the importance of expectancy beliefs and task values in influencing the motivational dynamics among learners.…”
Section: Introductionmentioning
confidence: 99%